Anthocyanins accumulation analysis of correlated genes by metabolome and transcriptome in green and purple peppers (Capsicum annuum) - Yaning Meng; Hongxiao Zhang; Yanqin Fan; Libin Yan (BMC Plant Biology, 2022)
Abstract Background In order to clarify the the molecular mechanism of anthocyanin accumulation in green and purple fruits of pepper using metabolomics and transcriptomics,to identify different anthocyanin metabolites,and to analyze the differentially expressed genes involved in anthocyanin biosynthesis.. Results We analyzed the anthocyanin metabolome and transcriptome data of the fruits of 2 purple pepper and 1 green pepper. A total of 5 anthocyanin metabolites and 2224 differentially expressed genes were identified between the green and purple fruits of pepper. Among the 5 anthocyanin metabolites,delphin chloride was unique to purple pepper fruits,which is the mainly responsible for the purple fruit color of pepper. A total of 59 unigenes encoding 7 enzymes were identified as candidate genes involved in anthocyanin biosynthesis in pepper fruit. The six enzymes (PAL,C4H,CHI,DFR,ANS,UFGT) had higher expression levels except the F3H gene in purple compared with green fruits. In addition,seven transcription factors were also found in this study. These transcription factors may contribute to anthocyanin metabolite biosynthesis in the fruits of pepper. One of differentially expressed gene novel.2098 was founded. It was not annotated in NCBI. Though blast analysis we preliminarily considered that this gene related to MYB transcription factor and was involved in anthocyanin biosynthesis in pepper fruit. Conclusions Overall, the results of this study provide useful information for understanding anthocyanin accumulation and the molecular mechanism of anthocyanin biosynthesis in peppers.